Cannabis use amongst tinnitus patients: consumption patterns and attitudes - Mavedatnia, Dorsa; Levin, Marc; Lee, Jong W.; Hamour, Amr F.; Dizon, Kaye; Le, Trung (Université d'Ottawa | University of Ottawa, 2023)
Abstract Background Tinnitus has a significant impact on quality of life and causes considerable psychological distress. Cannabis is known to modulate neuron hyperexcitability, provide protection against auditory damage, and has been used for treatment for many diseases which have physiological similarities with tinnitus. The objective of this study was to survey patients presenting with tinnitus regarding their perspectives and usage patterns of cannabis. Methods Patients with a primary presenting complaint of tinnitus in a tertiary neuro-otology clinic completed a 18-item questionnaire assessing perception, attitudes, and cannabis usage patterns. Results Forty five patients completed the survey (mean age: 54.5 years, 31 females and 14 males). Overall, 96% of patients reported that they would consider cannabis as treatment for their tinnitus. Patients considered cannabis use for auditory symptoms (91%), and symptoms related to their tinnitus, such as emotional complaints (60%), sleep disturbances (64%), and functional disturbances (56%). 36% of patients had previously used cannabis and 22% of patients reported cannabis use at the time of the study. 80% of patients that were actively using cannabis reported that it helped with tinnitus-related symptoms, such as dizziness, anxiety, bodily pain, and sleep disturbances. Most patients would prefer to use edibles (62%), tablet (58%) and cream (47%) formulations of cannabis. Patients were concerned about the cost (29%), potential physical health implications (53%) and psychosocial side effects (60%) of cannabis. Over half of patients learned about cannabis from a friend or family member and only 22% of patients learned about cannabis from a physician or nurse. Conclusion Cannabis use is common amongst patients with tinnitus and current users of cannabis reported that it helped with their symptoms. Most patients would consider its use as a potential treatment to alleviate their tinnitus-related symptoms and are interested in learning more regarding its use. By understanding how cannabis is perceived by tinnitus patients, healthcare providers can provide appropriate patient education. Graphical abstract